Outcomes of a Medication Optimization Virtual Interdisciplinary Geriatric Specialist (MOVING) Program: A Feasibility Study - Joanne Man-Wai Ho; Eric To; Rebecca Sammy; Matei Stoian; Jennifer Man-Han Tung; Robert Jack Bodkin; Lindsay Cox; Tony Antoniou; Sophiya Benjamin (Adis, Springer Healthcare, 2023)
Abstract Background Adverse drug events among older adults result in significant mortality, morbidity and cost. This harm may be mitigated with appropriate prescribing and deprescribing. We sought to understand the prescribing outcomes of an interdisciplinary geriatric virtual consultation service. Methods We conducted a retrospective, before-and-after feasibility study to measure prescribing outcomes for a medication optimization virtual interdisciplinary geriatric specialist (MOVING) programme comprised of expertise from geriatric clinical pharmacology, pharmacy and psychiatry for older adults (aged ≥ 65 years) between June and December 2018, Ontario, Canada. The primary outcome was the number of distinct prescriptions and the presence of polypharmacy (defined as ≥ 4 medications) before and after the service. Secondary outcomes included the number of as needed and regularly administered prescriptions, number of potentially inappropriate prescriptions as defined by the Beers and STOPP criteria, and number of prescriptions for psychotropics, long-acting opioids and diabetic medications. Results We studied 40 patients with a mean age of 80.6 [standard deviation (SD) 8.8] years who received a MOVING consult. We found no significant change in the mean total number of prescriptions per patient before (12.02, SD 5.83) and after the intervention (11.58, SD 5.28), with a mean difference of −0.45 [95% confidence interval (CI) −0.94 to 0.04; p = 0.07]. We found statistically significant decreases in as needed prescriptions (mean difference − 0.30, 95% CI − 0.45 to − 0.15; p<0.001), and potentially harmful medications as identified by the Beers (mean difference −1.25, 95% CI −2.00 to −0.50; p = 0.002) and STOPP (mean difference −1.65, 95% CI −2.33 to −0.97; p < 0.001) scores. Without including the cost savings from hospital diversion by a MOVING consult, the costs of a MOVING consult were $545.80-$629.80 per person, compared with the costs associated with traditional in-person consults involving similar specialist clinical services ($904.89-$1270.69 per person). Conclusion A MOVING model of care is associated with decreases in prescriptions for potentially inappropriate medications in older adults. These findings support further evaluation to ascertain health system impacts.